KOMUNIKASI ANTAR PRIBADI BAGIAN PEMBINA DI BALAI BESAR REHABILITASI SOSIAL BINA DAKSA ( BBRSBD ) PROF. DR. R. SOEHARSO SURAKARTA DALAM MELAKUKAN PELAYANAN SISWA - Jarot, Faizal (KOMUNITAS, 2014)
Interpersonal  communication  is  a  communication  process  happened  between  two  or  more  people with  direct  face  to  face.  As  the  most  complete  and  the  most  perfect  communication,  interpersonal communication  is  very  potential  to  influence  or  to  persuade   others   so   that   interpersonal communication   plays   important   role   in  human  life.  This  study  aims  to  know  the  interpersonal communication  on  elder  at BBRSBD  Prof.  DR. R. Soeharso  Surakarta  in students  service.  This study uses  qualitative  methods.  The  primary  data  is  information  about  the  pattern  of  inter-  personal communication between  official  elder  with  students in  BBRSBD  Prof. DR. R. Soeharso Surakarta in student  services.  These  data were collected  throughinterview  method  with  the  elder  supervisors, officials  and  student  BBRSBD Prof.DR.  R. Soeharso Surakarta.  The results shows that official elder in BBRSBD Prof. DR. R.  Soeharso Surakarta provides counseling services to the students trough rehabilitation  guidance and motivation by using interpersonal communication  either verbal or nonverbal  even verbal and non-verbal simultaneously.  Verbal  communication  is a communication  that is done  by  oral  or written.  Particularly,  the  use  of  verbal  communication  in  the  form  of Indonesian language  and  writing,  it  can  be  seen  when  the  elder officer  providing  services  to  students  trough guidance. Non-verbal communication  is communication without using  words  or nonlinguistic.  The  use of  non-verbal  communication  in  BBRSBD Prof.  DR.  R.  Soeharso  Surakarta  is  a  siren  sound  (as mark  in  starting  a  meal),  image  symbol  of  wheelchairs  and  hand  movements  showing  a  certain direction  or command.  Meanwhile,  verbal  and  non-verbal  communication  simultaneously used by elder  in  BBRSBD  Prof.  DR.  R.  Soeharso  Surakarta  is Indonesian language  followed  by  the hand  movement,  for  example  in  serving  students  who are physically disabled and speech impaired at the same time